Լսողության խանգարում ունեցող նախադպրոցական տարիքի երեխաների գրավոր խոսքի զարգացման գործընթացում Հայաստանում կիրառվող ռուսական և շվեյցարական մեթոդիկաների վերլուծությունը - Մանուկյան, Ա. Վ.
Дан анализ двух используемых методик в Армении по развитию письменной речи у дошкольников с нарушениями слуха – российской и швейцарской. Показаны положительные стороны данных методик, на практике а также выявленные недостатки. Подчеркивается необходимость создания специальной программы для обучения дошкольников с нарушениями слуха. The analysis of two almost used techniques in Armenia for development of written language for preschool children with a hearing disorder – Russian and Swiss is given in the article . Positive sides of these techniques are shown, the having shortcomings are revealed in practice. Need of creation of the special program for training of preschool children with a hearing disorder is emphasized.
Keywords: Լսողության խանգարում ունեցող երեխաներ